Barbacenia graminifolia, a resurrection plant with high capacity of water retention - do Nascimento, Alex; Suguiyama, Vanessa Fuentes; Sanches, Rodrigo Fazani Esteves; Braga, Marcia R.; Silva, Emerson Alves da; Silva, João Paulo Naldi; Centeno, Danilo C. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2020)
•Barbacenia graminifolia is a Brazilian resurrection plant.•B. graminifolia can be classified as poikilochlorophyllous.•Photosynthesis is affected only after severe water deficit.•Despite the partial return of carbon assimilation, fluorescence is fully recovered.•Long-term responses as a homoiohydric plant. Desiccation tolerance (DT) in vegetative tissues is not a common ability, especially in Angiosperms. Barbacenia genus is distributed in tropical seasonally dry environments, such as rock outcrops, in South America. Some of the Barbacenia species are described as DT and are able to tolerate drastic water loss of their tissues during the desiccation process and to reestablish their metabolism after rehydration. In order to better understand this ability, we evaluated aspects related to leaf water status, gas exchange, photosynthetic pigments content and chlorophyll a fluorescence of B. graminifolia, during 32 days of water deprivation followed by rehydration. Carbon assimilation (A) remained active until the 24th day, when volumetric soil moisture was below 10%. Leaf relative water content (RWC) remained constant during 28 days of water withholding, decreasing significantly after this period, followed by the lowest gas exchange parameters and maximum quantum efficiency of photosystem II (Fv/Fm), and the highest degradation rates of chlorophyll and carotenoids in the course of the desiccation period. After rehydration, RWC was rapidly recovered, as well as Fv/Fm and photosynthetic parameters. This time frame was not enough for total recovery of A rates due, probably, to the slow restoration of chlorophyll a content. We classify, therefore, the species as a resurrection plant. Despite the similar decrease of photosynthetic rates found in other DT species before reaching the desiccated state, B. graminifolia maintains CO2 assimilation even under low soil water availability (10%) as physiological strategy when submitted to severe water deficit.